Tom Swift and His War Tank; Or, Doing His Bit for Uncle Sam - Appleton, Victor (Salt Lake City, UT : Project Gutenberg, 1997)
"Tom Swift and His War Tank; Or, Doing His Bit for Uncle Sam" by Victor Appleton is a novel published as Volume 21 in the original Tom Swift series. When America enters World War I, young inventor Tom Swift faces accusations of being a slacker while his friends enlist and sell liberty bonds. In truth, Tom is secretly developing an advanced war tank with revolutionary capabilities for the Allied forces. Working in complete secrecy, he must protect his invention from German spies while proving his patriotism to a doubting public. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Tom_Swift_and_His_War_Tank
Release date is 1997-06-01
Produced by Anthony Matonac
Keywords: Swift, Tom (Fictitious character) -- Juvenile fiction; Tanks (Military science) -- Juvenile fiction